General Pharmacology of KP-102 (GHRP-2), a Potent Growth Hormone-Releasing Peptide - Furuta, Sadayoshi; Shimada, Osafumi; Doi, Naomi; Ukai, Kiyoharu; Nakagawa, Terutake; Watanabe, Jyo; Imaizumic, Masakazu (Arzneimittelforschung, 2004)
The general pharmacological effects of the hexapeptide KP-102 (D-alanyl-3-(2-naphthyl)-D-alanyl-L-alanyl-L-tryptophyl - D -phenylalanyl - L -lysinamide dihy-drochloride, growth hormone-releasing peptide-2, GHRP-2, pralmorelin, CAS 158861-67-7), which potently promotes growth hormone (GH) release by acting at both hypothalamic and pituitary sites, were evaluated in various animal experimental models. The administration of KP-102 showed no obvious effect at a pharmacological dose on the central nervous system. KP-102 had no significant effect on the autonomic nervous system and smooth muscle except a slight and transient increase in spontaneous motility of isolated rabbit ileum and contraction of isolated guinea pig ileum at high doses. There was negligible effect on the respiratory and cardiovascular systems, digestive system, renal function and blood system after KP-102 treatment.These results suggest that KP-102 has no serious general pharmacological effects at dose levels showing GH-releasing activity in the experimental animals. Therefore, it is concluded that KP-102 will be a useful drug for the diagnosis of serious GH deficiency and for treatment of short stature.
Keywords: CAS 158861-67-7; Growth hormone-releasing peptide-2; KP-102, general pharmacology; Pralmorelin